Efektivitas Program Kur 0% Di Kabupaten Sigi - Dewi, Dinda Amartya; Bidin, Cici Rianty K.; Dewi, Pricylia Chintya (BISMA : Business and Management Journal, 2023)
People's Business Credit (KUR) is a credit guarantee program, in which this program is distributed to owners of micro, small and medium enterprises (MSMEs) who need additional loan funds for their businesses. The Sigi Regency Government created a 0% KUR Program for business owners to assist in providing venture capital. After the program is running, the guarantor institution ensures that the program has been running productively or effectively so that the KUR program distribution target is achieved. The type of research method used in this study is the method of effectiveness and qualitative. The purpose of this study was to analyze the effectiveness of the distribution of the 0% KUR program and the inhibiting factors for the effectiveness of the 0% KUR program. From the results of interviews with the Head of the Sigi Regency Cooperative and UKM Office, the Head of the UKM Section in Sigi Regency, and the Secretariat Team for the 0% KUR Program, it was explained that the objectives of the 0% KUR Program had been indirectly achieved because there were several business actors who had successfully passed the program but of the target set by 1,000 business actors, only 9 business actors passed. This provides real change by helping capital for business actors in Sigi Regency and improving the economy in Sigi Regency. It is hoped that the 0% KUR program in the future will have a positive impact, especially in the economic sector.